Wireless Sensor Network for Real Time Monitoring and Detection of Water Contamination (International Journal of Scientific Research and Management (IJSRM), 2016)
Clean drinking water is very important for the health of Human being. Water distribution system facilitates the delivery of water to consumers But this systems are prone to contamination – which may be intentional or accidental. Infrastructure of the drinking water distribution system is very complex in the environment. This paper gives a novel and low cost approach towards the problem of water quality monitoring. The paper focuses on developing low cost sensors for monitoring different water parameters. These sensors are in-pipe sensors and can be used for real time monitoring of the water quality in water distribution systems. A sensor array is developed based on some important water parameters. selected water parameters are pH, Turbidity, Electrical Conductivity and Temperature. A circuit for analog signals conditioning, processing is also developed.